PTU-058 Histological liver collagen proportionate area predicts decompensation in patients with liver cirrhosis of mixed aetiologies. (23rd September 2015) - Isgro, G; Calvaruso, V; Manousou, P; Luong, T; Alibrandi, A; Garcovich, M; Tsochatzis, E; Dionigi, E; Patch, D; O'Beirne, J; Dhillon, A; Burroughs, A
Abstract : Introduction: Histological scoring systems diagnose cirrhosis, but not severity of cirrhosis. Computer assisted digital image analysis (DIA) of Sirius red stained sections measures fibrosis morphologically, using segmentation of digital images to measure the relative areas of collagen and of tissue, producing a fibrosis ratio or collagen proportionate area (CPA).1 CPA could have staging and prognostic value for histological cirrhosis. The aim of this study is to evaluate CPA in cirrhosis of mixed aetiology and its relationship with liver decompensation. Methods: We evaluated 118 consecutive patients with histological cirrhosis retrospectively: 76 males, mean age 53(±12.31), follow-up mean of 41.6 (±22.03) months after biopsy. At biopsy 63 were compensated (no ascites, bleeding episodes, encephalopaty). Results: The mean CPA value in compensated patients was 17.2 (±8.3), in decompensated patients 27.9 (±10.7) (p<0.0001). Mean time to first decompensation was 47(± 21) months. The AUROC for CPA to future decompensation in the compensated group was 0.80 (95% CI 0.71 to 0.88). The best cut-off was 20.1 (80% sensitivity and 78%specificity). Decompensation within 24 months had an AUROC of 0.79 (95% CI 0.63 to 0.96) and best cut-off was 18.1 (80% sensitivity and 80% specificity). Cox regression for time to decompensation was evaluated using INR, bilirubin, albumin, sodium, creatinine, Child score and CPA. Indipendently associated variables were CPA (OR 1.13, 95% CI 1.06 to 1.22, p=0.001) and albumin (OR 0.13, 95% CI 0.03 to 0.54, p=0.005). Conclusion: CPA increases with worsening cirrhosis and is able to predict decompensation in compensated cirrhosis of mixed aetiologies. This suggests that severity of cirrhosis can be assessed histologically and that it correlates with clinical outcome.